TRANSFORMASI KEBIJAKAN PENDIDIKAN ISLAM DI ERA DIGITAL: TANTANGAN DAN STRATEGI MANAJEMEN INOVASI - Hafizh Taufiq Fadlur Rahman; Ice Rosina Sari; Betty Anggoro Weni; Ammirudin; Tin Amalia Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The digital revolution has changed the paradigm of contemporary Islamic education, where technological disruption demands profound policy transformation to bridge the gap between traditional Islamic education systems and the demands of the digital age. This phenomenon reflects the dialectic between classical Islamic scholarship and technological modernity, which often poses challenges in maintaining spiritual identity while adopting pedagogical innovations. The urgency of this transformation is increasingly evident with the emergence of the digital divide, where access to technology is uneven, thereby affecting the effectiveness of Islamic values-based learning.This study aims to analyze the transformation of Islamic education policy in the digital era, identify systemic and structural challenges, and formulate applicable and sustainable innovation management strategies. Using a qualitative approach through library research, this study explores the latest literature to provide an in-depth understanding of this phenomenon, with a phenomenological perspective that emphasizes contextual interpretation.The main findings indicate that the primary challenges include resistance to cultural change, limitations in digital infrastructure, and inadequate educator competencies. Key strategies include integrating technology with Islamic values, capacity building through continuous training, and collaborative governance involving multiple stakeholders. The policy implications encourage the development of an adaptive Islamic education model, where technology is not a threat but a means of spiritual and intellectual revitalization.In conclusion, innovation management is a key pillar in the transformation of Islamic education, requiring strategic commitment from stakeholders to overcome challenges and take advantage of digital opportunities. Strategic recommendations include strengthening responsive regulations, investing in infrastructure, and fostering a culture of sustainable innovation. This research contributes to the development of more inclusive and sustainable Islamic education policies, bridging the gap between tradition and modernity in a global context.